Psychographic Factors of Millenial Consumers Influenced by MSMEs’ Traditional Food Product Purchase Decisions - assegaf, Safira; Irianto , Heru; Mulya Handayani, Sugiharti (Neo Journal of economy and social humanities, 2022)
The goal of this study was to see how psychographic elements from the millennial generation influenced MSMEs' purchasing decisions for traditional food products. Psychographic elements in this study were lifestyle, social class, consumer personality traits, and income. Knowing which of the four variables is the most influential is also important. The sample was taken using survey techniques, and the method employed in this study is descriptive. By purposefully selecting the sample requirements, the research location is Surakarta City. The 400-sample method of determining the sample. Residents of Surakarta aged 21 to 41 years are the sample criterion for the millennial generation. The data analysis approach, on the other hand, was SEM, which was examined with AMOS 22 software. The results of the SEM analysis suggest that the goodness of fit is generally good and may be deemed to meet the model fit, specifically CMIN/Df = 2.85; TLI= 0.97; CFI= 0.98; NFI= 0.97; IFI= 0.98; IFI= 0.98; RMSEA= 0.07; GFI = 0.95 AGFI 0.9. The model's estimation results show that lifestyle influences purchasing decisions (p= 0.00; cr= 5.463), social class influences purchasing decisions (p= 0.00; cr= 1.96) and consumer personality traits influence purchasing decisions (p= 0,00; cr= 13,019), and income influences purchasing decisions (p= 0,00; cr= 12,195). The results of earlier studies are typically supported by the relationship between the variables in this study's structural equation model. The consumer personality character variable has the biggest influence (p = 0.00; cr = 13, 019) on the decision to buy traditional food goods from MSMEs (p = 0.00; cr = 13, 019).